A Foresight Study on Baby Boomers towards Using Robots in Replacing Carts at Supermarkets - Mazli, Hannan Nur Ain; Azizan, Anim Zalina (Research in Management of Technology and Business, 2023)
Even with the use of robots to replace carts, it appears that the method is a new and creative way for Baby Boomers to use the convenience of robots in supermarkets. However, there are concerns about the effectiveness of using robots, as they are not yet popular enough among Baby Boomers to take over the place of carts. Therefore, this study aims to identify the issues, challenges, trends, and drivers of the use of robots to replace carts in supermarkets and to explore future images of the use of robots in replacing carts in supermarkets. In the investigation, a mixed approach of qualitative and quantitative methods was used. A tool of foresight methodology, the STEEPV method was used in the first phase of identifying the issues, challenges, trends, and drivers of the use of robots to replace carts. The distribution and SPSS statistical analysis were used to identify the two drivers of robot adoption in supermarkets in the second phase of the investigation with impact-uncertainty analysis. The result of the two drivers are robots observe the condition of the item, and robots encourage and guide consumer where an item is placed. A scenario analysis formulation has been constructed in conjunction with the two drivers that provide insight into four possible alternatives within the time horizon of the next few years. The two drivers have a strong correlation where both selected drivers must coexist to generate a positive scenario for the development and sustainability of the technology and robotics sector.